A Mayfly for Prof. Hegel: Herbart's Forgotten Review of Hegel's Rechtsphilosophie. Issue 3 (2nd October 2021) - Beiser, Frederick
ABSTRACT: Herbart and Hegel were contemporaries and both became famous, in their time and thereafter. It would be interesting therefore to know what they thought of one another. We could easily answer this question if they reviewed one another. Hegel never reviewed Herbart; but Herbart did review Hegel. Though in his later years Herbart protested that he did not want to engage with Hegel, he had already written, in 1822, one of his longest and most important reviews, which was of Hegel's Philosophie des Rechts . Herbart maintained that there is a Spinozistic element to Hegel's political philosophy which equates right with might. Hegel tried to avoid the implications of this equation by bringing Kantian transcendental freedom into his system, which for him boiled down to the idea of dialectical development. But Herbart rejected the fundamental idea behind dialectical development: that the ego posits the opposite of itself. Herbart then criticized Hegel's attempt to revive natural law and his theory of the state. Herbart contended that reason cannot prove the fundamental principles of natural law, that reason by itself is an abstract and formal power and as such cannot demonstrate any principle having substantive content. And Herbart criticized Hegel's doctrine that the individual finds his identity only in the state. Much more liberal than Hegel, Herbart stressed the importance of individuality outside the state.